Personal Recovery in People With a Psychotic Disorder: A Systematic Review and Meta-Analysis of Associated Factors - Leendertse, J. C. P.; Wierdsma, A. I.; van den Berg, D.; Ruissen, A. M.; Slade, M.; Castelein, S.; Mulder, C. L. (Frontiers in Psychiatry, 2021)
Background: Personal recovery (PR) is a subjective, multidimensional concept, and quantitative research using PR as an outcome is rapidly increasing. This systematic review is intended to support the design of interventions that contribute to PR in psychotic disorders, by providing an overview of associated factors and their weighted importance to PR: clinical factors, social factors, and socio-demographic characteristics are included, and factors related to the concept of PR (organized into CHIME dimensions). Methods: A systematic literature search was conducted from inception to March 2020. Quantitative studies that had used a validated questionnaire assessing the concept of PR were included. Mean effect sizes for the relationship between PR-scale total scores and related factors were calculated using meta-analyses. Sources of heterogeneity were examined using meta-regression tests. Results: Forty-six studies, that used [a total of] eight PR measures, showed that in clinical factors, affective symptoms had a medium negative association with PR-scale total scores (r=-.44, 95%CI -0.50 to -0.37), while positive, negative and general symptoms had small negative correlations. No association was found with neuro-cognition. Social factors (support, work and housing, and functioning) showed small positive correlations. Gender and age differences had barely been researched. Large associations were found for PR-scale total scores with the CHIME dimensions hope (r=.56, 95%CI 0.48 to 0.63), meaning in life (r=.48, 95%CI 0.38 to 0.58) and empowerment (r=.53, 95%CI 0.42 to 0.63); while medium associations were found with connectedness (r=.34, 95%CI 0.43 to 0.65) and identity (r=.43, 95%CI 0.35 to 0.50). Levels of heterogeneity were high, sources included: the variety of PR measures, variations in sample characteristics, publication bias, variations in outcome measures, and cultural differences. Discussion: Most interventions in mental healthcare aim to reduce symptoms and improve functioning. With regard to stimulating PR, these interventions may benefit from also focusing on enhancing hope, empowerment and meaning in life. The strength of these findings is limited by the challenges of comparing separate CHIME dimensions with questionnaires assessing the concept of PR, and by the high levels of heterogeneity observed. Future research should focus on the interaction between elements of PR and clinical and social factors over time.